Darrieus vertical axis wind turbine for power generation I: Assessment of Darrieus VAWT configurations. (March 2015) - Tjiu, Willy; Marnoto, Tjukup; Mat, Sohif; Ruslan, Mohd Hafidz; Sopian, Kamaruzzaman
Abstract: This paper aims to assess the Darrieus vertical axis wind turbine (VAWT) configurations, including the drawbacks of each variation that hindered the development into large scale rotor. A comprehensive timeline is given as a lineage chart. The variations are assessed on the performance, components and operational reliability. In addition, current development and future prospects of Darrieus VAWT are presented. The Darrieus VAWT patented in France in 1925 and in the US in 1931 had two configurations: (i) curved blades and (ii) straight blades configurations. Curved blades configuration (egg-beater or phi-rotor) has evolved from the conventional guy-wires support into fixed-on-tower and cantilevered versions. Straight blades configuration used to have variable-geometry (Musgrove-rotor), variable-pitch (Giromill), Diamond, Delta and V/Y rotor variations. They were stopped due to low economical value, i.e. high specific cost of energy (COE). Musgrove-rotor has evolved into fixed-pitch straight-bladed H-rotor (referred as H-rotor in this paper for simplicity). H-rotor, in turn, has evolved into several variations: Articulating, Tilted and Helical H-rotors. Graphical abstract: Highlights: A comprehensive timeline of Darrieus VAWT development. Assessment of all Darrieus VAWT variations from several aspects. Current development and future prospects of Darrieus VAWT. Curved blades guy-wired phi-rotor has evolved into cantilevered phi-rotor. Straight blades at present (H-rotor): Fixed-pitch, Articulating, Tilted and Helical.